2016
DOI: 10.1007/s13744-016-0442-6
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Storage of Telenomus remus (Nixon) (Hymenoptera: Platygastridae) and its Factitious Host Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae)

Abstract: We conducted three bioassays to evaluate the effect of low-temperature storage of eggs (host) and pupae and adults (parasitoid) on the biology and parasitism capacity of the egg parasitoid Telenomus remus (Nixon) (Hymenoptera: Platygastridae). Viable stored Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) eggs were parasitized to the same degree or even higher than fresh eggs when stored until 14 days at 5°C or until 21 days at 10°C. In contrast, the percentage of parasitized sterilized eggs was equal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
5
21
2
Order By: Relevance
“…Our results showed that while the placement of viable H. halys egg masses at a relatively high average temperature (22.9ºC) for 4-7 days had a negative impact on parasitism levels and fitness parameters of emerging parasitoids, these reductions in parasitoid emergence and fitness were not observed for refrigerated eggs or in either treatment at a lower average temperature (13.4ºC). The decrease in T. japonicus emergence and body weight and the increase in development time with increasing physiological age of viable H. halys eggs is in agreement with results from other studies (Qiu 2007;Yang et al 2018). Since the H. halys embryo is developing in untreated eggs (and this progresses faster at warmer temperatures), host resources and quality for immature parasitoids are likely declining (Barrett and Schmidt 1991;Vinson 2010;Skillman et al 2017).…”
Section: Applications For Field Monitoringsupporting
confidence: 90%
“…Our results showed that while the placement of viable H. halys egg masses at a relatively high average temperature (22.9ºC) for 4-7 days had a negative impact on parasitism levels and fitness parameters of emerging parasitoids, these reductions in parasitoid emergence and fitness were not observed for refrigerated eggs or in either treatment at a lower average temperature (13.4ºC). The decrease in T. japonicus emergence and body weight and the increase in development time with increasing physiological age of viable H. halys eggs is in agreement with results from other studies (Qiu 2007;Yang et al 2018). Since the H. halys embryo is developing in untreated eggs (and this progresses faster at warmer temperatures), host resources and quality for immature parasitoids are likely declining (Barrett and Schmidt 1991;Vinson 2010;Skillman et al 2017).…”
Section: Applications For Field Monitoringsupporting
confidence: 90%
“…An important finding of our study is that the sex ratio of T. podisi offspring was not affected by storage of E. heros eggs at any of the three tested temperatures and generally remained at 0.86 or higher, with a minimum of 0.72. Higher numbers of females are considered important in ABC because males do not contribute directly for parasitism-induced declines in pest populations (Navarro 1998;Queiroz et al 2017). A similar sex ratio was considered to be of acceptable quality in mass production of other egg parasitoids such as Trichogramma pratissolii (Querino & Zucchi) (Hymenoptera: Trichogrammatidae) (van Lenteren 2003).…”
Section: Storage (Days)mentioning
confidence: 99%
“…Apart from host availability, one of the major difficulties in mass rearing of egg parasitoids in the laboratory is the necessity of releasing them immediately after adult emergence, due to the adults' short life span (Queiroz et al 2017). Although T. podisi has a longer life span than T. remus, this still applies to both species.…”
Section: Storage (Days)mentioning
confidence: 99%
See 2 more Smart Citations